2014
DOI: 10.1128/genomea.00451-14
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Novel Reassortant Mammalian Orthoreovirus Strain MRV00304/13, Isolated from a Calf with Diarrhea from the United States

Abstract: Mammalian orthoreovirus (MRV) strain MRV00304/13 was isolated from diarrheic calves. The serotype-specific antigen σ1 was found to be 95% identical to that of bovine MRV1. All predicted viral proteins had >92% identity to those of MRV except µ2 and σ1s (80 and 72% identities, respectively), suggesting that MRV00304/13 is a novel reassortant MRV1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…However, in the last decade, increasing numbers of studies in humans and other mammals have shown that they can cause severe illness in humans and other mammals, including upper respiratory tract infections, encephalitis, and diarrhea (Chua et al, 2008;Ouattara et al, 2011a;Steyer et al, 2013a). MRVs have been isolated from a broad range of mammalian species, including bats (Hu et al, 2014;Kohl et al, 2012;Lelli et al, 2013;Lorusso et al, 2014;Thalmann et al, 2010;Wang et al, 2015a;Yang et al, 2015), civet cats , cows (Anbalagan et al, 2014), mink (Lian et al, 2013), pigs (Dai et al, 2012b;Kwon et al, 2012b;Thimmasandra Narayanappa et al, 2015;Zhang et al, 2011a), dogs (Decaro et al, 2005) and humans (Chua et al, 2008;Ouattara et al, 2011b). However, porcine MRV failed to arouse the concern of researchers until 2007, when it was first reported as the cause of diarrhea in newborn piglets in China (Zhang et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the last decade, increasing numbers of studies in humans and other mammals have shown that they can cause severe illness in humans and other mammals, including upper respiratory tract infections, encephalitis, and diarrhea (Chua et al, 2008;Ouattara et al, 2011a;Steyer et al, 2013a). MRVs have been isolated from a broad range of mammalian species, including bats (Hu et al, 2014;Kohl et al, 2012;Lelli et al, 2013;Lorusso et al, 2014;Thalmann et al, 2010;Wang et al, 2015a;Yang et al, 2015), civet cats , cows (Anbalagan et al, 2014), mink (Lian et al, 2013), pigs (Dai et al, 2012b;Kwon et al, 2012b;Thimmasandra Narayanappa et al, 2015;Zhang et al, 2011a), dogs (Decaro et al, 2005) and humans (Chua et al, 2008;Ouattara et al, 2011b). However, porcine MRV failed to arouse the concern of researchers until 2007, when it was first reported as the cause of diarrhea in newborn piglets in China (Zhang et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Although MRVs are widely distributed in humans, livestock and wild animals in Asia, Europe and North, and South America [2,16,[19][20][21][22][23][24][25][26][27]29], they have never been detected from pigs in Africa and their epidemiological information in Africa is limited. In this study, we report the isolation and characterization of MRVs circulating in a pig population in Zambia.…”
Section: Discussionmentioning
confidence: 99%
“…MRVs have been identified in humans, livestock and wild animals with a wide host range [2,[19][20][21][22][23][24][25][26]. Individual MRVs can infect multiple species; several interspecies transmission and genetic reassortment events involving both humans and animals have been reported [2,[15][16][17][18][19][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Three large segment (L1, L2, L3), three medium size segments (M1, M2, M3), and four small segments (S1, S2, S3, and S4) Genome encased in a double concentric icosahedral capsid shell (inner shell or core and outer shell) Gene segments are transcribed into full-length mRNAs Gene segments encode one or two proteins: k, l, and r size class proteins Food Environ Virol MRV (Anbalagan et al 2014;Lelli et al 2015). Studies have indicated that 75 % of the RNA (15 9 10 6 Daltons) in the virion is contained in these 10 dsRNA segments, while about 25 % of the RNA in the virions ( *4.5 9 10 6 Daltons) is composed of short single-stranded adenylic-rich oligonucleotides.…”
Section: Organization Of the Reov Particle And Genomementioning
confidence: 99%